Formation of Planetary Consciousness and the Noosphere Mentality of the Universities’ Students as a Condition for Sustainable Development - TERENTIEVA, NATALIIA; YASHNIK, SVETLANA (Journal of Education, Technology and Computer Science, 2017)
The article represented the idea that universities as centers of formation of the new thinking noosphere, noosphere consciousness perform another function center for training specialists in sustainable development society. The University is regarded as the center of human formation, which has critical and innovative thinking, able to continuous self-development and self-improvement for the purpose of self-realization.